Finite element modeling in obstetrics and gynecology: advances, applications, and challenges - Moseley, Taylor; Hicks, Ashley J.; Cosgriff-Hernandez, Elizabeth M.; Rausch, Manuel Karl; Hakim, Julie (Frontiers in Medicine, 2025)
Finite element modeling (FEM) is a critical tool in biomechanics and biomedical engineering, offering valuable insights where in vivo or ex vivo investigations are not possible. This review specifically highlights the diverse applications of FEM within obstetrics and gynecology through a comprehensive analysis of the literature. We explore the past use of FEM in analyzing complications affecting pelvic floor structures, urinary continence, and reproduction. The potential contributions of FEM in addressing these challenges are summarized and future directions for its application in obstetrics and gynecology are highlighted.